Analysis of The Use of Promotion In Social Media on The Performance of E-Commerce Marketing - Ariep, Zaenal (STEKOM PRESS, 2021)
Social media is a new phenomenon that has changed the way the business environment operates. Through social media, businesses gain access to resources that are otherwise unavailable to the business owner. This research is a causality research, which aims to analyze the causal relationship and influence of two or more phenomena, through hypothesis testing. The population and sample in this study are SMEs who open e-commerce businesses on social media. The number of samples used in this study amounted to 154 respondents. Based on the analysis and discussion, it is concluded that the Marketing operation advantages variable has no significant effect on Marketing Performance, the Cost-effectiveness variable has a significant effect on Marketing Performance, the Customer Communication Channel variable has a significant effect on Cost-effectiveness, the Customer Communication Channel variable has a significant effect on Increased customer satisfaction, Customer The Communication Channel has a significant effect on Marketing operation advantages, the Customer relationship performance variable has a significant effect on Marketing Performance, the Increased customer satisfaction variable has a significant effect on Marketing Performance and the Social media marketing implementation capabilities variable has a significant effect on Customer relationship performance.